Legal Issues and Tax Burdens in the Personal Income Taxation of Independent Professionals - Nitithammanart, Nugul (Rajapark Journal, 2026)
This research aims to: 1) study the concepts, theories, and principles regarding personal income tax collection for independent professionals; 2) examine the legal provisions and criteria for personal income tax collection from independent professionals under Thai law, and compare them with relevant foreign laws; 3) analyze legal issues in taxing independent professionals, particularly concerning expense deductions under the Revenue Code; and 4) propose guidelines for amending tax laws and measures to ensure equity and suitability for the current socio-economic environment. This study employs a qualitative documentary research methodology. Data was collected from laws, rules, regulations, academic texts, articles, the Revenue Code, official orders, and practical guidelines, including relevant publications in both Thai and foreign languages. The gathered data were systematically organized, analyzed, and synthesized qualitatively. A literature review was conducted to formulate recommendations for amending personal income tax regulations and expense deduction criteria for income derived from independent professions under the Revenue Code. The research findings reveal the following: 1) The core concepts, theories, and principles relevant to tax collection are grounded in the principles of a good tax system and equity. 2) A comparative study with the legal frameworks of France and Australia shows that these countries do not categorize independent professions into distinct types. 3) The current system, which applies varying expense deduction criteria for different types of independent professions, leads to inequity. 4) Therefore, it is recommended to amend and clearly redefine the provisions in the Revenue Code. Specifically, the criteria for expense deductions should be restructured to ensure equal fairness, and the sub-categorization of independent professions should be abolished.